Analisis Pengaruh Penataan Muatan terhadap Stabilitas Kapal dan Keselamatan Operasional Kapal di MV. Hanglima - Freddy Nicholus Kandou; Mudiyanto Mudiyanto; Dedy Kristiawan (Port Management and Maritime Administration Journal, 2026)
This study was conducted based on the importance of implementing proper cargo stowage procedures to maintain ship stability and improve operational safety during voyages on board MV. Hanglima. Improper cargo stowage may alter the ship's center of gravity, thereby increasing the risk of rolling, pitching, and cargo shifting, which may endanger navigational safety. This study aims to analyze the effect of cargo stowage on ship stability and operational safety aboard MV. Hanglima. The research employed a quantitative method with an explanatory research design. The study involved 31 respondents selected using a saturated sampling technique. Data were collected through questionnaires distributed to the ship's crew and analyzed using validity tests, reliability tests, descriptive statistical analysis, classical assumption tests, and simple linear regression analysis with the assistance of SPSS software. The results indicate that cargo stowage has a positive and significant effect on ship stability, with a significance value of 0.000 and a coefficient of determination (R²) of 0.787. Furthermore, cargo stowage also has a positive and significant effect on ship operational safety, with a significance value of 0.000 and a coefficient of determination (R²) of 0.637. Therefore, the better the implementation of cargo stowage procedures, the better the ship's stability and operational safety. The findings of this study are expected to provide valuable input for shipping companies and ship crews in optimizing the implementation of cargo stowage procedures in accordance with maritime safety standards.